Initial Analysis of Plant Soil for Evidence of Pathogens Associated with a Disease of Seedling Ocotea monteverdensis - William D. Eaton; Debra A. Hamilton; Alexander Lemenze; Patricia Soteropoulos (Microorganisms, 2025)
Seedlings of the ecologically important, critically endangered tree Ocotea monteverdensisis experience high mortality in the Monteverde, Costa Rica, cloud forests at the onset of the wet season, yet there are no studies suggesting the disease etiology. Here, healthy and diseased plant root and bulk soils were analyzed for various carbon and nitrogen (N) metrics and respiration levels, and DNA sequence-based bacterial and fungal community compositions. All nitrogen metric levels were greater in diseased vs. healthy plant root soils, which could enhance pathogen growth and pathogenic mechanisms. Greater DNA percentages from several potential pathogens were found in diseased vs. healthy plant root soils, suggesting this disease may be associated with a root pathogen. The DNA of the fungus Mycosphaerella was at greater levels in diseased vs. healthy plant root soils than other potential pathogens. Mycosphaerella causes similar diseases in other plants, including coffee, after onset of the wet season. The O. monteverdensis disease also occurs in seedlings planted within or near former coffee plantations at wet season onset. Distance-based linear model analyses indicated that NO3− levels best predicted the pattern of fungal pathogens in the soils, and Mycosphaerella and Tremella best predicted the patterns of the different N metrics in the soils, supporting their possible roles in this disease.